Effect of plant ontogeny on quantity and chemical constituents of essential oil in sweet basil (Ocimum basilicum l.) grown in Sudan - Aburigal, Yasmin A. A.; Mirghani, Mohamed Elwathig Saeed; Elmogtaba, Elfadly Y.; Sirible, Awatif M.; Hamza, Nada B.; Hussein, Ismail H. (IIUM Press, 2020)
Sweet basil (Ocimum basilicum L.) is a very important food additive as well as for its therapeutic and cosmetic potential. The composition of essential oils in plants is affected by genetics and environmental conditions, which is determined by the growth region and harvesting time in terms of ontogenetical variability. This study was carried out to assess the effect of plant ontogeny (pre-flowering, at flowering, fruiting) on essential oil content and chemical constituents for four sweet basil cultivated under irrigation conditions in the experimental farm of the National Oilseed Processing Research Institute (NOPRI), University of Gezira, Sudan. The essential oils were hydro-distilled from the leaves using Clevenger apparatus and the chemical constituents were determined by GCMS. The results reveal that the essential oil yield content ranged from 0.1% to 0.2% at preflowering stage, whereas the oil content obtained at the post-flowering stage was 0.1% for the investigated accessions. The highest essential oil content was recorded at the flowering stage (0.2-0.5%), where the two Sudanese accessions had the maximum content (0.5%). The major chemical constituents, linalool, citral, methyl eugenol, and eucalyptol reported at different developmental stages, punctuated between 5.73% and 32.93% in the four investigated accessions.